The Effect of Application of Group Activity Therapy Session 1-2 on Controlling Hallucinations - Rosmiati Rosmiati; Mohamad Saoky Miswar; Aulia Ridla Fauzi (LPPM STIKes Muhammadiyah Ciamis, 2023)
Hallucinatory disorders are one of the nursing problems that can be found in patients with mental disorders. One of the most common types of hallucinations is auditory hallucinations. Auditory hallucinations can be ringing sounds or noises that have no meaning, but are more often heard as a meaningful word or sentence. One therapy for hallucinations is Group Activity Therapy (TAK). Objective: To determine the effect of group activity therapy sessions 1-2 on controlling hallucinations. Methods: This study uses a quantitative method with a quasi experiment. Sampling with purposive sampling technique is as many as 6 respondents. This study was conducted on March 15-23 2022. Results: showed that patients with hallucinations were able to control hallucinations after the implementation of TAK Sessions 1-2 with the results of comparative analysis, the pretest 3.7, posttest 8.4 and p value=0.01. Conclusion: there is an effect of group activity therapy sessions 1-2 on controlling hallucinations in hallucinating patients.